Pengaruh Keseimbangan Kehidupan Kerja (Work Life Balance) dan Kepuasan Kerja Terhadap Komitmen Organisasi Guru SD Negeri di Kecamatan Kota Masohi - Achmat Riffay (Peneliti.net, 2019)
The objective of this research is to know the effect of work life balance and job sastisfaction toward teacher’s commitment organization of the private vocational high school at Masohi district east Masohi. The research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 772 teachers. Research samples selected as much as 263 teachers using simple random sampling technique. The data obtained through questionnaires and analyzed using path analysis techniques. Based on the results of data analysis in this research it is concluded: (1) the work life balance have positive direct effect to Comittment organization; (2) job sastisfaction have positive direct effect to Comittment organization; (3) the work life balance have positive direct effect to job sastisfaction. The Comittment organization can be improved through improvement of work life balance and job sastisfaction.